Environmental drivers of microbial community shifts in the giant barrel sponge, X estospongia muta , over a shallow to mesophotic depth gradient - Kathleen M. Morrow; Cara L. Fiore; Michael P. Lesser (Environmental Microbiology, 2016)
Summary The giant barrel sponge, X estospongia muta , is a high microbial abundance sponge found on Caribbean coral reefs along shallow to mesophotic depth gradients where multiple abiotic factors change with depth. Sponges were collected along a depth gradient at L ittle C ayman ( LC ) and Lee Stocking Island ( LSI ), and the microbiome of these samples was analysed using 16 S r RNA amplicon sequencing. Statistically significant shifts in community structure and dissimilarity (∼ 40%) were detected from 10 to 90 m in LC sponges, but a similar shift was not identified in sponges from 10 to 60 m at LSI (only 17% dissimilar). Additionally, inorganic nutrient levels steadily increased with depth at LSI but not at LC . Based on bulk stable isotopic variability, sponges collected from LC were generally more enriched in 15 N and less enriched in 13 C as depth increased, suggesting a transition from dependency on photoautotrophy to heterotrophy as depth increased. Patterns of stable isotopic enrichment were largely invariant at LSI , which is also reflected in the more stable microbial community along the depth gradient. It appears that environmental factors that change with depth may contribute to differences in X . muta microbial assemblages, demonstrating the importance of contemporaneous environmental sampling in studies of the microbiome of sponges.